The structural characteristics of the lifestyle among older adults and its impact on the health in China - Xiaohui Wang; Haimin Miao; Qiaosen Jin (Frontiers Media S.A., 2023)
ObjectiveEnhancing overall health remains a primary global objective, with lifestyle being a crucial factor impacting the health status among older adults. This study focuses on the lifestyle of Chinese older adults, systematically exploring the evolution and characteristics of their lifestyle and investigating its impact on their health.MethodsUtilizing panel data from the Chinese Longitudinal Health Longevity Survey (CLHLS) from 2008, 2011, 2014, and 2018, we adopted 15 indicators reflecting older adults' lifestyle. Latent class analysis and ordinary least square regression were used to uncover the structural nuances of the Chinese older adults' lifestyle and its effects on health.ResultsThe study identifies three distinct lifestyle categories for the older adults: relatively positive, mixed, and relatively negative. It reveals that the Chinese older adults do not predominantly adopt a positive lifestyle, and this trend persisted from 2008 to 2018. Each improvement in lifestyle category significantly boosts the older adults' physical health, mental health, and self-assessed health by 11.2%, 3.6%, and 17.1%, respectively.ConclusionTo attain the strategic aim of healthy aging, efforts should prioritize encouraging the older adults to adopt a positive lifestyle, enhance the geriatric health service system, and promote an intelligent lifestyle management model.